2016
DOI: 10.1097/ncc.0000000000000252
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Clusters in Ovarian Cancer Patients With Chemotherapy After Surgery

Abstract: The ability to predict symptom clusters in ovarian cancer patients receiving chemotherapy may help to make optimized clinical decision in advance to alleviate patients' symptoms and improve their life quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
82
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(95 citation statements)
references
References 49 publications
12
82
0
1
Order By: Relevance
“…Of the few self-reported symptom studies that have been conducted in patients with ovarian cancer, our results are comparable with 2 studies using MSAS, where mean numbers of reported symptoms were 11.2 9 and 10.0, 24 compared with 10.7 in our study. The most prevalent symptoms reported in the study by Portenoy et al 9 were pain, lack of energy, worrying, feeling sad, feeling nervous, and insomnia, which are identical with the most prevalent symptoms in our study, whereas the 5 symptoms with highest prevalence in the study by Huang et al 24 were lack of energy, hair loss, difficulty sleeping, lack of appetite, and anxiety. Thus, lack of energy seems to be a predominant symptom across different studies.…”
Section: Discussionsupporting
confidence: 85%
“…Of the few self-reported symptom studies that have been conducted in patients with ovarian cancer, our results are comparable with 2 studies using MSAS, where mean numbers of reported symptoms were 11.2 9 and 10.0, 24 compared with 10.7 in our study. The most prevalent symptoms reported in the study by Portenoy et al 9 were pain, lack of energy, worrying, feeling sad, feeling nervous, and insomnia, which are identical with the most prevalent symptoms in our study, whereas the 5 symptoms with highest prevalence in the study by Huang et al 24 were lack of energy, hair loss, difficulty sleeping, lack of appetite, and anxiety. Thus, lack of energy seems to be a predominant symptom across different studies.…”
Section: Discussionsupporting
confidence: 85%
“…To our knowledge, no other lung cancer study used the MSAS (which assesses multiple skin, hair, mouth, and appearance symptoms) to identify symptom clusters. However, when the MSAS was used in studies of patients with breast cancer, 24 ovarian cancer, 56 and a heterogeneous group of cancer diagnoses, 57 a similar epithelial symptom cluster was found. Further research is needed to confirm the presence of an epithelial cluster in lung cancer patients.…”
Section: Discussionmentioning
confidence: 92%
“…When the symptoms in our epithelial symptom cluster were compared to previous studies of symptom clusters in oncology patients receiving CTX that used the MSAS, three studies identified an image-related cutaneous symptom cluster (Suwisith et al, 2008) or a body image symptom cluster (Huang et al, 2016; Molassiotis et al, 2010). In the study that included only patients with breast cancer (Suwisith et al, 2008), hair loss, change in the way food tastes, mouth sores, and changes in skin were included in the image-related cutaneous symptom cluster.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms included in this cluster that were identified in patients <60 years of age but not in patients ≥60 years of age were: sweats, difficulty sleeping, pain, and weight gain. In a study that evaluated patients with ovarian cancer receiving CTX (Huang et al, 2016), a menopausal symptom cluster was identified. However, sweats were the only common symptom included in their hormonal symptom cluster.…”
Section: Discussionmentioning
confidence: 99%